Analisis Lalu Lintas Ruas Jalan Denpasar-Gilimanuk Tabanan Bali Masa Pendemi Covid 19 - Hidayat, Dwi Wahyu; Mardikawati, Budi; Oktopianto, Yogi; Shofiah, Siti (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2021)
Tabanan Regency is one of the regencies that is traversed by the main route connecting Gilimanuk-Denpasar so that the road is known as Jalan Raya Denpasar-Gilimanuk. The road is a National Road which is the main route connecting the districts in western Bali, namely Jembrana Regency, Tabanan Regency, Badung Regency and Denpasar City. In addition, with the increasing activities of the Tabanan community, especially those in the city of Tabanan who travel either to the city of Denpasar or to other areas, passing through this route which is the main route that serves transportation activities from Tabanan to Denpasar and vice versa. In this location there are many places that cause attraction, namely shopping centers, stalls and places of worship. Therefore, congestion on these roads often occurs, especially at peak hours of traffic flow (Peak Hour). This research was conducted on the performance of roads to determine the level of service. The data analysis process uses the method of calculating the Manual Kapasitas Jalan Indonesia (MKJI) 1997). The results showed that the Tabanan-Denpasar road, Jl Ahmad Yani, during the COVID-19 pandemic PPKM level 4 was obtained, the road capacity was 2,457 smp/hour, the free flow speed was 46.48 km/hour, the degree of saturation was 0.79, the light vehicle speed value was 36 km/hour with a travel time of 25 seconds. Based on the value of the degree of saturation on the Tabanan-Denpasar road, Jl Ahmad Yani during the COVID-19 pandemic PPKM level 4 of 0.79, then the level of service for the road was entered at Service level D.